Peran Jamaluddin Al-Afghani Dalam Membentuk Isu-Isu Pembaharuan Pemikiran Islam: The Role of Jamaluddin Al-Afghani in Shaping the Issues of Islamic Intellectual Renewal - Yogi Hajrian Syah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study examines Jamaluddin Al-Afghani's strategic role in formulating and articulating key issues of Islamic intellectual renewal in the late 19th century. Through historical-philosophical analysis of his writings, particularly in Al-Urwah Al-Wuthqa, this research explores how Al-Afghani constructed an integrated reform agenda linking Pan-Islamism, anti-colonial resistance, educational modernization, and religious rationalism as interconnected solutions to the challenges facing the Muslim world. Findings reveal that Al-Afghani employed sophisticated framing strategies to present reform as both a religious imperative and political necessity, thereby creating a durable foundation for Islamic modernism. His approach successfully bridged Islamic tradition with modern demands while advocating Muslim unity against Western colonial domination. This study concludes that Al-Afghani's methodological innovation shifted Islamic intellectual discourse from defensive responses to proactive agenda-setting, significantly influencing subsequent reform movements across the Muslim world.